Description of Difficulties in Implementing The Assessment of Performance Aspects for Understanding Mathemathic Teachers at MTs Al Mustaqim Parepare - Sari, Vernita (Study Program of Mathematics Education University of Muhammadiyah Malang, 2018)
Performance assessment needs to understand and implement by teachers sothat the teachers can assess the skills aspects of their studentswell. However, some teachers have difficulties in implementingperformance assessment includes mathematic teachers at MTs Al MustaqimParepare. The purpose of this research is to describe the difficulties ofimplementing performance assessment on understanding aspects ofmathematic teachers at MTs Al Mustaqim Parepare. This research wasqualitative research. The subjects of the study were two mathematic teachersof MTs Al-Mustaqim Parepare here in after called subject 1 (H) and subject2 (N). The focus of the research is to describe the difficulties teachers usingthe performance assessment on aspects of teachers' understanding ofmathematic. For revealing the research data, this conducts tests andinterviews to the subject of research. The data of research is validated bydoing triangulation method. The Research of data is analyzed by (a)studying the subject data and comparing data to obtain for valid data, (b)reducing data by creating abstractions, (c) classifying and identifying thedata to draw conclusions from the data. The result research shows thatthe difficulties for teachers, it is for understanding aspect about theassessment performance. For instance, (a) the subject 1 (H) was difficult inunderstanding about the concept of assessment, (b) the subject 1 (H) wasdifficult in understanding the assessment techniques so that it can beimplemented, (c) subject 1 (H) was difficult in understanding the types ofassessment rubrics, and (d) subject 2 (N) was difficult in understanding theconcept of assessment.